2013
DOI: 10.1002/cne.23450
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and subcellular heterogeneity of GLAST and GLT‐1 immunoreactivity in the developing postnatal mouse hippocampus

Abstract: Astrocytes express two sodium-coupled transporters, glutamate-aspartate transporter (GLAST) and glutamate transporter-1 (GLT-1), which are essential for the maintenance of low extracellular glutamate levels. We performed a comparative analysis of the laminar and subcellular expression profile of GLAST and GLT-1 in the developing postnatal mouse hippocampus by using immunohistochemistry and western blotting and employing high-resolution fluorescence microscopy. Astrocytes were identified by costaining with glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 88 publications
(120 reference statements)
11
54
4
Order By: Relevance
“…For both GLT-1 and GLAST several distinct bands (60,130, 180 kd and 55, 130, 150, 190 kd, respectively) were detected in all age groups most likely due to monomeric and multimeric fractions of the transporters ( Figure 7A), confirming earlier studies indicating that both exist as homomultimers [45,46]. Numerical analysis of GLT-1 expression (60, 130, 180 kDa) revealed a steady increase in relative protein content during postnatal development (N = 4 per age group) as shown before for mouse hippocampus [43]. At the neonatal stage (P5), GLT-1 expression was low (10.4%) compared to P25 (100%).…”
Section: Spatial and Developmental Expression Profile Of Glutamate-assupporting
confidence: 89%
See 3 more Smart Citations
“…For both GLT-1 and GLAST several distinct bands (60,130, 180 kd and 55, 130, 150, 190 kd, respectively) were detected in all age groups most likely due to monomeric and multimeric fractions of the transporters ( Figure 7A), confirming earlier studies indicating that both exist as homomultimers [45,46]. Numerical analysis of GLT-1 expression (60, 130, 180 kDa) revealed a steady increase in relative protein content during postnatal development (N = 4 per age group) as shown before for mouse hippocampus [43]. At the neonatal stage (P5), GLT-1 expression was low (10.4%) compared to P25 (100%).…”
Section: Spatial and Developmental Expression Profile Of Glutamate-assupporting
confidence: 89%
“…While the GLAST protein expression level significantly rose from P5 to P10 (87.6%), there was no further significant increase at P15 (74.0%) as compared to P25 (N = 3 per age group) ( Figure 7B). Again, this general expression profile was similar to that reported from early postnatal hippocampus [43].…”
Section: Spatial and Developmental Expression Profile Of Glutamate-assupporting
confidence: 86%
See 2 more Smart Citations
“…GLT-1 also has several known isoforms, which have been found to be differentially distributed at the regional, cellular and subcellular level in astrocytes in the hippocampus, lateral septum, cerebral cortex and striatum, in neurons, in photoreceptors of the retina, and in the liver (Patel and Klein, 2011;Jitoku et al, 2011;Magnotti et al, 2011;Lehre et al, 1995;Schmitt et al, 2002;Schreiner et al, 2014;Rauen et al, 2004). Several studies have reported GLT-1 expression by mature oligodendrocytes (DeSilva et al, 2009;Domercq et al, 2005;Werner et al, 2001), although that has been disputed by other investigators, who have reported that GLT-1 expression is lost in mature oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%